OPTIMALISASI PEMANTAUAN SUHU DAN KELEMBABAN COLD STORAGE DENGAN DATA LOGGER ELITECH RC4 HC: ANALISIS KASUS DI PT. DELTA MINA PERKASA - Azizah, Imrotul; Daging, I Ketut; Nazaruddin, Nazaruddin (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2025)
Cold storage is an important facility in the fishing industry to extend the shelf life of products, especially frozen fish, while maintaining their quality. This research analyzes the performance of the Elitech RC4 HC Data Logger in monitoring temperature and humidity in a 400-ton capacity cold storage at PT Delta Mina Perkasa, Sidoarjo, East Java. Research methods include surveys, direct observation, interviews, and internships, with descriptive and quantitative data analysis approaches. Data loggers were placed at three points: near the door, the middle section with load, and the back section without load, to record temperature and humidity conditions for 78 days. The results showed that the best temperature and humidity stability was recorded in the center of the cold storage, while the largest temperature fluctuations occurred near the door, caused by door opening and closing activities. In June, the cold storage conditions were considered good, but the quality of frozen fish decreased during July to September due to machine repairs. Overall, the Elitech RC4 HC Data Logger proved effective in monitoring real-time temperature and humidity conditions. However, to maintain the quality of frozen fish consistently, it is recommended that the company adds specialized humidity monitors, improves cold storage management, and conducts regular monitoring.